STUDY OF SEASONAL BIOLOGICAL BACTERIAL INTESTINAL INFECTIONS IN THE EXAMPLE OF ESHERICHIA (Journal of Universal Science Research, 2023)
The family of intestinal bacteria includes bacteria that are very close to each other from an evolutionary point of view, but differ in pathogenicity and some characteristics, mainly living in the intestines of humans or vertebrates. Enterobacteria (Enterobacteriaceae) family includes 14 genera: Escherichia; Klebsiella; Proteus, Yersinia, Erwinia, Shigella, Salmonella, Enterobaster, Citrobacter, Hafnia, Serratia, Pro'idencia, Morganella, Edwarosiela. The seed is divided into types, and the type is divided into biological, serological, hemological and other options.